Penggunaan teknologi informasi untuk mengelola data imunisasi dan gizi pada posyandu Kureksari kecamatan Waru Sidoarjo - Slamet Slamet; Siswo Martono; I Gusti Alit Widana P; Ferdiansyah Darmawan (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2022)
Posyandu is one of the main programs of the Government of Indonesia related to public health services, especially for the health of infants, toddlers and pregnant women. Routine activities carried out by posyandu include monitoring pregnant women, monitoring growth and providing immunizations for infants, toddlers and pregnant women. Posyandu is usually driven by selected cadres with guidance from health workers in their area. The Sakura Posyandu located in Kureksari Village, Waru District, Sidoarjo Regency has activities that empower and provide convenience to the community in obtaining basic health services. The main goal is to reduce maternal and infant mortality. In the management of immunization and nutrition data, the data input process is still carried out in two stages, namely by entering the cadres' books and maternal and child health books. This often results in redundancy and data loss, in addition to inefficient time and asynchronous data between the original and stored data. Therefore, it is necessary to apply immunization and nutrition data management at the Sakura Posyandu to facilitate the management of the data they have. As a result, the processing process becomes more efficient, there is no duplicate data and data retrieval becomes faster.